Human Rights - the Way Forward - Kirby, Justice Micheal (Victoria University of Wellington Law Review, 2000)
The following paper was presented at the inaugural Michael Hirschfeld Memorial Address hosted by the Amnesty International Freedom Foundation on 30 October 1999. Michael Hirschfeld was instrumental in establishing the Freedom Foundation in 1989. He wanted to help stabilise Amnesty International's financial base in order to guarantee the organisation's research and international campaigning efforts against gross human rights violations such as unfair imprisonment, torture and killings. His death at the beginning of 1999 shocked and saddened fellow Freedom Foundation members who determined to establish this annual event to honour his memory and his commitment to international human rights.